Thermoelectric properties of hot pressed CZTS micro spheres synthesized by microwave method. (13th February 2018) - Sharma, Sarita Devi; Neeleshwar, Sonnathi
ABSTRACT: Microwave synthesis of Copper Zinc Tin Sulphide (CZTS) sphere like particles has been demonstrated. The structural and morphological properties of CZTS particles are characterized by XRD, SEM and Raman spectroscopy and subsequently thermoelectric properties are investigated. XRD results of prepared powder sample matches well with tetragonal crystal structure of CZTS bulk. No other impurity phase has been detected from the XRD analysis. Raman spectrum further confirms the formation of single phase CZTS with characteristics peak for CZTS at 334.1 cm -1 . SEM studies reveal that the CZTS particles are spherical in shape with uniform sizes of ∼ 250-350 nm. Hot pressed CZTS system shows a power factor ∼21 µW/mK 2 and ZT∼ 0.024 at 623 K. Significant enhancement in the Figure of merit for CZTS system is observed in comparison to reported nanostructures of the same system may be due to increased electrical conductivity.